S = 1 + 1 2 + 1 4 1 + 1 + 2 2 + 2 4 2 + 1 + 3 2 + 3 4 3 + ⋯
For S as defined above, find 1 4 S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir, this time I could break it till the third step, but I don't understand the fifth step: 2 1 × 0 + 0 + 1 1 How can this be reached? Thanks!
Log in to reply
I have added a step to explain. It is just n = 0 .
Log in to reply
Oh, I understood. Brilliant solution! Thank you!
why do u repost it?
@Razing Thunder , please use only three dots ... \dots or \cdots for infinite terms. Please do not add ∞ at the end (however much you like it). It can mean the term tense to ∞ . The three dots are international professional standards used in all proper math materials.
Problem Loading...
Note Loading...
Set Loading...
The sum S can be rewritten as:
S = n = 1 ∑ ∞ 1 + n 2 + n 4 n = n = 1 ∑ ∞ ( n 2 − n + 1 ) ( n 2 + n + 1 ) n = n = 1 ∑ ∞ 2 1 ( n 2 − n + 1 1 − n 2 + n + 1 1 ) = 2 1 n = 1 ∑ ∞ ( ( n − 1 ) 2 + ( n − 1 ) + 1 1 − n 2 + n + 1 1 ) = 2 1 ( n = 0 ∑ ∞ n 2 + n + 1 1 − n = 1 ∑ ∞ n 2 + n + 1 1 ) = 2 1 × 0 2 + 0 + 1 1 = 2 1
Therefore 1 4 S = 1 4 × 2 1 = 7 .